Strategi Pengembangan Sport Event Rafting Berbasis Komunitas Di Kabupaten Lahat, Provinsi Sumatera Selatan - Wisanggeni Agus Priyanto; Muhammad Iqbal Djohan; Dilla Pratiyudha Sayangbatti (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2022)
This research focuses on the development of sport event rafting as a community-based special interest tourism product considering that Lahat Regency will host the Provincial Level Sports Week in South Sumatra in 2023. This study aims to determine the form of planning, implementation, evaluation and strategy owned by community-based sport rafting event in Lahat Regency in managing it as a Sports Tourism-based tourist destination. The method used is the mix method, which is a combination of quantitative and qualitative. For the quantitative approach, data collection techniques were used using random sampling with accidental sampling, while for the qualitative approach, data collection techniques were used using non-probability sampling with accidental sampling. For representative results, researchers took a number of 35 respondents. Analysis of the data used through the Miles and Huberman models. To test the validity using the triangulation method. Based on the results of the study, the SWOT analysis shows that the results of external and internal analysis obtained a combination of SO/strength and opportunity to get the highest score with a total value of 6.60, it is meaning that the determination of priority program indicators can be carried out by referring to mapping and encouraging special access from toll roads so that tourists get ease of accessibility to enjoy the natural landscape and tourist spots, especially rafting in Lahat Regency, as well as making river zoning for sports/competition and for family rafting. Keywords: Sport Event; River Tourism; Development Strategy